Two Stories of Wage Dynamics in Latin America: Different Policies, Different Outcomes. - Canavire-Bacarreza, Gustavo; Carvajal-Osorio, Luis C. (Journal of Labor Research, 2020)
This article explores the variation in the wage distributions of two Latin American countries, Bolivia and Colombia, which have had different political and economic strategies in recent years. Using data from household surveys, a decomposition of the wage distribution in each country using functional principal component analysis is conducted. The results suggest that Bolivia, which has implemented state-centered policies, has experienced a general increase in wages, especially benefiting the least skilled workers and the informal sector. On the other hand, the wage distribution in Colombia, whose economic policy has leaned towards market-oriented principles, has become more concentrated around the median wage, mainly due to changes in formal sector wages.